PENGEMBANGAN MEDIA FLASH CARD MATH BERBASIS CODE QR PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN NUMERACY SKILL SISWA KELAS V DI UPT SDN TLOGO 02 KABUPATEN BLITAR - Anisa Salsabela; Ragil Tri Oktaviani; Khoirul Wafa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Numeracy skill is a person's ability to solve problems by processing data using basic mathematics. This ability needs to be instilled in students to help them face problems in the 21st century. The aim of this research is to determine the development, level of validity and feasibility of QR code-based flash card media and also to increase numeracy skills before and after learning using the media that has been developed. This research uses instruments in the form of questionnaires, tests and also documentation in its implementation. This research is research & development (R&D) research with the ADDIE (analyze, design, development, implementation, evaluation) development model. The results of this research show that the media validity level received a score of 93.18% from media experts and a score of 100% from material experts and is included in the very valid category. The level of media suitability carried out by researchers received a score of 94.4% and was included in the category that is suitable for use without the need for revision. Apart from that, it is known that there has been an increase in the processing of test results carried out by researchers with a mean value of 0.5039 so that it is included in the moderate improvement category.